2020
DOI: 10.4103/ijmr.ijmr_2234_20
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers & SARS-CoV-2 infection in India: A case-control investigation in the time of COVID-19

Abstract: Background & objectives: Healthcare workers (HCWs) are at an elevated risk of contracting COVID-19. While intense occupational exposure associated with aerosol-generating procedures underlines the necessity of using personal protective equipment (PPE) by HCWs, high-transmission efficiency of the causative agent [severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)] could also lead to infections beyond such settings. Hydroxychloroquine (HCQ), a repurposed antimalarial drug, was empirically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(98 citation statements)
references
References 34 publications
2
95
1
Order By: Relevance
“…CQ/ HCQ can prevent viral entry has been demonstrated by Wang et al 30 through their time-of-addition studies. Based on these encouraging preclinical trials and supported further by preliminary internal observational studies, 31 prior to exposure. It was also observed that among HCQ takers 32 were exposed to a symptomatic contact out of which only 3 (9.38%) were positive whereas in the control group 33 were exposed to a symptomatic contact out of which 18 (54.55%) tested to be positive.…”
Section: Discussionmentioning
confidence: 80%
“…CQ/ HCQ can prevent viral entry has been demonstrated by Wang et al 30 through their time-of-addition studies. Based on these encouraging preclinical trials and supported further by preliminary internal observational studies, 31 prior to exposure. It was also observed that among HCQ takers 32 were exposed to a symptomatic contact out of which only 3 (9.38%) were positive whereas in the control group 33 were exposed to a symptomatic contact out of which 18 (54.55%) tested to be positive.…”
Section: Discussionmentioning
confidence: 80%
“…A number of recent studies have endorsed these concerns including the UK Recovery Trial (171,(176)(177)(178), resulting in the WHO and the National Institute of Health (NIH) in the US halting the use of hydroxychloroquine in their studies (161,167,177,179,180). However, hydroxychloroquine is still recommended for prophylaxis in India with Chatterjee et al (181) demonstrating that hydroxychloroquine was associated with a significant reduction in the chances of healthcare workers getting COVID-19 (21,181,182). The Government and others in Malaysia also initially endorsed hydroxychloroquine helped by additional supplies from India (183), with continued endorsement at lower doses in early June (8,184,185), with the Government in Pakistan banning exports for fear of shortages (186), although later reversed (187).…”
Section: Management Strategies To Prevent and Treat Covid-19 -Generalmentioning
confidence: 99%
“…6 A total of 22 studies including HCWs were registered on clinicaltrials.gov, and 6 of them were already recruiting subjects. 7 On May 31st, Chatterjee et al published a case-control study, in which they found an association between HCQ administration and a lower risk of disease 8 ; this study was the first one to suggest the prophylactic efficacy of HCQ among HCWs. On the other hand, continuous treatment with HCQ did not prevent SARS-CoV-2 infection in a large database analysis.…”
mentioning
confidence: 94%